RISK FACTORS OF STUNTING EVENTS IN CHILDREN IN THE WORKING AREA OF PANDAN PUBLIC HEALTH CENTER, SINTANG REGENCY - Elvi Juliansyah Jamari; Agustini - Elisabet (Dian Nuswantoro Semarang, 2021)
Stunting is a nutritional problem seen from the inappropriate length or height according to age. Nutritional status was monitored through the TB / U index. From the data from the Puskesmas Pandanus, the prevalence of stunting is 31.71% in 2018 of the total 719 children under five. This research aims to determine the risk factors for stunting in the work area of the Pandan Community Health Center, Sintang District. This type of research is quantitative using a cross sectional approach with a population of mothers who have children under five as many as 719 and this sample is 257 mothers under five. The primary data collection tool used a questionnaire using a survey method for mothers of toddlers who were used as samples in this study to obtain primary data. The results of this study are based on statistical tests known that associated with the incidence of stunting in children under five is parenting (p = 0.011), tradition (p = 0.001), and access to information (p = 0.003). All parties related to the incidence of stunting in toddlers teach good parenting by reducing traditions that have an impact on the health of toddlers, and constantly convey the importance of toddler health for the future.